1988
DOI: 10.1007/bf00429985
|View full text |Cite
|
Sign up to set email alerts
|

Cocarcinogenic and tumor-promoting capabilities of anthralin

Abstract: Numerous chemicals to which humans are exposed either therapeutically or as a result of living in an industrial environment constitute a potential threat as carcinogens, mutagens, and/or tumor promoters and cocarcinogens. Anthralin, and antipsoriatic agent, acts as a tumor promoter for Balb/c-3T3 mouse embryo cell cultures that were previously exposed to a low dose of either benzo-a-pyrene (BaP), an indirect-acting carcinogen needing metabolic conversion for its carcinogenic action, or beta-propiolactone (BPL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…When the present results are compared to the published data on in vitro cell transformation (1,3,4,(23)(24)(25)(26)(27)(28)(29) and in vivo carcinogenicity (from the IARC and CCRIS databases; Table 3), a correlation was observed for B[a]P, MMS, phenanthrene, mezerein, and PDD. In accordance with the reported carcinogenicity of phenacetin, our results from the initiation assay indicated a positive designation when the appropriate doses were used, as discussed earlier.…”
Section: Control Cultures In All Experimentsmentioning
confidence: 65%
See 1 more Smart Citation
“…When the present results are compared to the published data on in vitro cell transformation (1,3,4,(23)(24)(25)(26)(27)(28)(29) and in vivo carcinogenicity (from the IARC and CCRIS databases; Table 3), a correlation was observed for B[a]P, MMS, phenanthrene, mezerein, and PDD. In accordance with the reported carcinogenicity of phenacetin, our results from the initiation assay indicated a positive designation when the appropriate doses were used, as discussed earlier.…”
Section: Control Cultures In All Experimentsmentioning
confidence: 65%
“…Discordant results for anthralin, phenacetin and phorbol were produced, between the present promotion assay and the in vivo promoter assay. The published data on anthralin indicate positive results for both cell transformation (26,27) and in vivo carcinogenicity (30). Phenacetin acted as a promoter in the renal tract, in animals which had some burden to predispose them to renal tract carcinogenesis (31)(32)(33).…”
Section: Control Cultures In All Experimentsmentioning
confidence: 99%
“…The cytotoxicity of 5 and 6 was compared with CP (1) in a mouse embryo Balb/c 3T3 cell line. 21 The LC50 value for compound 5 (21.8 µ ) indicated that it was only slightly more active than 1 (37.6 µ ). Compound 6 was considerably more cytotoxic than either 1 or 5 with a LC50 value of 0.6 µ (Table 1).…”
Section: Biological Results and Discussionmentioning
confidence: 99%
“…From our results, it appears that anthralin specifically enhances the genetic effects induced by UV (Kunz et al 1980) and UV-mimetic agent 4-NQO (our data) but not by gamma radiation. Similarly, selective enhancement of neoplastic transformation by anthralin was observed with B(a) P but not with β-propiolactone (Baturay and Trombetta 1988). However, very little information is available in literature regarding the modifying effects of anthralin for a wide variety of DNA damaging agents having different mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…Since then it has become a widely used, safe and highly effective topical remedy for the treatment of chronic plaque psoriasis. Anthralin has also been shown to exhibit potent tumour-promoting activities (Bock and Burns 1963;Segal et al 1971;Baturay and Trombetta 1988;DiGiovanni et al 1988) A number of studies have been carried out to study the potentiating effects of tumour promoters on the genotoxic effects induced by carcinogens in vitro. Trosko et al (1977) have demonstrated that the well-known tumour promoter 12-O-tetradecanoylphorbal-13-acetate (TPA) enhanced UV-induced mutations in mammalian cells, and chemical carcinogens' induced mutations in Salmonella typhimurium and CHO cells.…”
Section: Introductionmentioning
confidence: 99%